Molecular cardiovascular imaging - Dobrucki, Lawrence W.; Sinusas, Albert J. (Current cardiology reports, 2005)
Imaging with radionuclides has historically played an important role in detection of cardiovascular disease as well as in risk stratification and prognostication. With the growth of molecular biology have come new therapeutic interventions and the requirement for new diagnostic imaging approaches. Noninvasive targeted radiotracer-based strategies require the development of new instrumentation to meet these needs. This progress has been made possible with the availability of many technologic advances, which include dedicated micro single-photon emission computed tomography (SPECT) and micro positron emission tomography (PET) hybrid systems for small animal imaging. This review is a brief overview on the subject of molecular imaging. Basic concepts of molecular imaging are reviewed, followed by description of current technologic advances, and current applications to evaluate ischemic heart disease and potential therapeutic intervention. The emphasis is on the use of both SPECT and PET radiotracers, although other imaging modalities are also briefly discussed.